INNOVATIVE AND CREATIVE TEACHING TECHNOLOGIES IN FOREIGN LANGUAGE CLASSES - Abdisalimova Kamola Sanjar qizi (Bright Mind Publishing, 2025)
This article examines innovative and creative teaching technologies used in foreign language classes. It highlights modern pedagogical approaches, digital tools, and interactive methods that enhance learners’ communicative competence, motivation, and critical thinking skills. The study emphasizes learner-centered instruction, the integration of information and communication technologies, and the role of creativity in developing effective language learning environments. The application of these technologies contributes to improving the quality and effectiveness of foreign language education.
Keywords: Innovative technologies, creative teaching, foreign language education, interactive methods, digital tools, learner-centered approach, communicative competence.